Valorization of Vigna radiata (l.) Wilczek. and Moringa oleifera to improve food recipes of 6-23-month-old children in northern Benin - Bankole, Malikath; Bodjrenou, Sam; Honfo, Fernande; Codo, Gloria; Bodecker, Julia; Termote, Céline; Chadare, Flora; Amoussa Hounkpatin, Waliou (Elsevier, 2023)
Biodiversity valorization is one way to improve food choices and contribute to a diversified diet among households. This paper aimed to valorize Vigna radiata (l.) Wilczek. and Moringa oleifera to improve food recipes of 6-23-month-old children. Two local recipes (Zankpiti and Abobo) were formulated from these plant species. The formulation was done with Minitab software, version 18 using the mixing design. The optimized recipes were tested through a hedonic test by 62 children in three (03) communes. The nutritional densities of accepted recipes were then determined. The hedonic test showed that 83.33% and 82.69% of children respectively appreciated Abobo of mung bean with moringa leaves (AMM) and Zankpiti of mung bean (ZM). Regarding the nutritional densities, energy and vitamin A densities of the recipes were largely above the recommended standards (2.03 ± 0.02 kcal/g and 1085.18 ± 14.56 RE μg/100 kcal for ZM; 1.72 ± 0.08 kcal/g and 1028.8 ± 74.1 RE μg/100 kcal for AMM. The nutritional densities of iron, calcium and zinc did not meet the recommended standards. Regarding the cover rates of the daily children's needs, both recipes had very high cover rates in vitamin A and low levels in daily calcium requirements. ZM had covered interesting daily requirements rate up to 37.64 ± 25.56%, 15.82 ± 10.75%, 24.94 ± 16.94% and 919.43 ± 624.82% respectively for energy, zinc, iron and vitamin A while AMM recipe covered high rates up to 36.36 ± 30.73% for energy and 655.38 ± 537.07% for vitamin A. These two plant species in children's feeding can also contribute to a better coverage of children's daily requirements.